HEPATIC STEATOSIS IN SCHOOLCHILDREN AND ADOLESCENTS WITH CENTRAL OBESITY - Lalaleo Portero, Tannia Jacqueline (2022)
Introduction: Non-alcoholic hepatic steatosis is defined as the excessive accumulation of adipose tissue in the absence of alcohol consumption, being rare in the pediatric population. However, with the advent of the twentieth century pandemic, such as obesity, this pathology has increased its incidence, as well as others that belong to the metabolic syndrome. Objective: To determine the presence of hepatic steatosis in schoolchildren and adolescents with central obesity. Methods: observational, descriptive and cross-sectional research. The sample was of a census type, represented by 32 schoolchildren and adolescents who met the inclusion criteria, which are: age between 6 and 19 with central obesity - prior signing the informed consent. They underwent measurement of the waist circumference, abdominal ultrasound, measurement of the lipid profile and the determination of the level of physical activity through the application of the Pictorial Questionnaire of Infant Physical Activity. Results: 32 patients were studied, 18 (56.3%) male, adolescents 59.37%. With normal ultrasound (29/32) and with hepatic steatosis (3/32), of which 66.7% are grade II and 33.3% are grade III. Hypertriglyceridemia and borderline triglyceride levels 81.27% and hypercholesterolemia and borderline cholesterol levels 75%. Conclusion: School and adolescent patients with central obesity have borderline lipid profiles or dyslipidemia, in which, despite belonging to the pediatric population, moderate and severe cases of hepatic steatosis are evident. Keywords: fatty liver, non-alcoholic fatty liver disease, dyslipidemia, obesity.